Advantage of multichannel intraluminal impedance in the diagnosis of aerophagia: a case report - Aya Tanaka; Takayuki Fujii; Hiroto Katami; Ryuichi Shimono (BMC, 2024)
Abstract Background Aerophagia is caused by the swallowing of excessive air and associated with various gastrointestinal symptoms. Aerophagia is diagnosed based on the observation of the occurrence of excessive air swallowing or ingestion; however, it tends to be difficult and often delayed. Early recognition and diagnosis of aerophagia are required to avoid unnecessary diagnostic investigations or serious clinical complications. Given that multichannel intraluminal impedance-pH measurement can discriminate gas, liquid, and mixed swallows, it can be useful for the diagnosis of aerophagia. Case presentation A 7-year-old girl presented to us with vomiting, and abdominal radiography showed dilatation of the stomach and intestine with no signs of mechanical obstruction. After successful conservative treatment, her symptoms recurred. Along with frequent visible and audible air swallowing, computed tomography (CT) revealed a severely dilated stomach with organoaxial volvulus. Multichannel intraluminal impedance-pH measurement was performed for further exploration. Patients showed numerous air swallows, particularly in the daytime during the 24-h recording period. She was diagnosed with aerophagia complicated by gastric volvulus. Given that she had a mental disorder and psychological counseling was difficult, laparoscopic anterior gastropexy and gastrostomy were performed to correct the gastric volvulus and decompression of gastric dilation by gastrostomy. Conclusions In addition to clinical symptoms, multichannel intraluminal impedance-pH measurement may help more accurately and objectively diagnose aerophagia. Further studies of air swallowing patterns may be useful for understanding the pathophysiological mechanism of aerophagia.